(untitled) - Drummond, Richard Henry (Grand Rapids, Mich., 1971)
A history of Christianity in Japan is a Christian world mission book, belonging to the series on " Discipling the Nations in the great era of world mission now ended. The seven series deal with very aspect of the world mission of the church of Christ, history, theory, methods, functional approaches, regional studies, biography, and source materials of exceptional,...
Keywords: Missions,Japan; Church history; Japan